Gender roles and smoking behaviour - Priska Flandorfer; Christian Wegner; Isabella Buber (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2010)
The gender gap in smoking prevalence is closing in several developed countries due to decreasing smoking rates among men and increasing among women. Previous studies present a variety of hypotheses with the central argument that the process of gender equality is related to the declining trend regarding sex differences in smoking. We suppose that changes in traditional gender roles have influenced the smoking behaviour among both men and women. Our study focuses on the stereotypical masculine behaviour pattern which is assumed to be a smoking determinant and is increasingly adopted by females now. We applied a triangulation (combination) of qualitative and quantitative methods. The results indicate a connection between gender roles and health behaviour, especially smoking behaviour. The knowledge and experience of physicians reveal that although the attribute 'masculinity' is related to a higher risk of smoking it is increasingly adopted by women. The dynamic is further influenced by factors like age, social norms, workforce participation as well as mediaand leads to a change of perceived gender roles in society. This fact can partly explain the increasing amount of smoking women. From a methodological point of view the current study is an example for a successful triangulation of quantitative and qualitative methods. Precisely because both methods have different angles-the qualitative one focusing on the knowledge and experiences of physicians and the quantitative one on individual behaviour style-the results complement each other and yield a comprehensive picture.
Keywords: 300; Triangulation; gender roles; smoking behaviour; gender gap; Geschlecht; Soziale Rolle; Rauchen; Welt